GE_GERICHTE P/16541/2012 vom 18. November 2013 - GE Cour de justice (2013)
MENDICITÉ; DROIT FONDAMENTAL; CONFISCATION(DROIT PÉNAL) | CPP.398.4; CPP.263; CEDH.10.1; Cst.8.2; LPG.11A; RPSS.4; RTP.1; CP.70.1